Influence of Chromium Doping on the Structural and Optical Properties of Zinc Sulfide Thin Films Prepared via Spray Pyrolysis - Asmaa Mohammed Raoof, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In this study, doping impact of Chromium (Cr) on the actual properties of Zinc Sulphide (ZnS) at different content of (0, 2, and 4 wt % Cr) was discussed. The considered examples were readied utilizing Spraying Technique. Other published papers matched structural, topographical, and optical characterization in similar writings. X-ray diffraction reveals the high peak matched (008) plane; grain size is set to increase from 12.23 to 13.44 nm with Chromium doping. In contrast, the dislocation density decreases from 66.85 to 55.36, while strain decreases from 28.33 to 25.79. AFM images indicate that average particle size was 63.3 nm to 31.89 nm with Undoped ZnS and ZnS: Cr with 0% and 4% concentrations, respectively. Transmittance offers good transparency, in the visible area between 68 and 63, for undoped ZnS and 4% Cr content. The absorption coefficient indices increased via increasing Chromium doping. The optical bandgap of undoped ZnS and ZnS:Cr films decreases from 3.47 eV to 3.37 eV as the chromium concentration increases from 0% to 4%. The extinction coefficient and refractive index decrease via increasing Chromium doping.
Keywords: ZnS thin film; Cr; structural; topography; Optical Properties; bandgap